JURIDICAL ANALYSIS OF THE CASE OF INTOXICATION FROM BOILING SANITARY PADS VIEWED FROM LAW NO. 35 OF 2009 ON NARCOTICS - Witri Safitri; Tedjabuana, Rosa (Rechtsregel : Jurnal Ilmu Hukum, 2025)
The phenomenon of intoxication from sanitary pad decoction among adolescents and vulnerable groups reflects regulatory gaps as well as weak legal and health awareness. This case raises serious issues because the substances involved are not listed as narcotics or psychotropics under Law Number 35 of 2009, yet they produce hallucinogenic effects similar to narcotics. This study aims to analyze the phenomenon of sanitary pad decoction intoxication from a criminal law perspective, while also considering social and health aspects. The research applies a normative juridical approach through statutory review, document analysis, literature studies, and case reviews. Data were obtained from relevant legislation, scientific literature, and documented cases that occurred in several regions.The findings indicate that this practice cannot easily be prosecuted under the Narcotics Law due to the legality principle, despite its harmful impact on health and potential social disruption. Law enforcement officers can only apply alternative measures through the Health Law, the Penal Code, or local regulations concerning public health and order. This study highlights a normative legal vacuum in addressing non-conventional substance abuse, emphasizing the need for revising the Narcotics Law or establishing specific regulations that are more responsive. The contribution of this study lies in enriching the discourse on criminal law and public protection, while encouraging adaptive policies to anticipate alternative substance abuse beyond conventional narcotics.